Performance Comparison of SBS Modified and Fatty Amine Modified Asphalt Mixes - Aksoy, Atakan; Iskender, Erol; Oruc, Seref; Ozen, Halit (TURKISH CHAMBER CIVIL ENGINEERS, 2012)
Performance Comparison of SBS Modified and Fatty Amine Modified Asphalt Mixes The purpose of this study is to compare the performances of SBS polymer and fatty amine modified asphalt mixtures. With the laboratory produced traditional and modified Marshall Briquettes, three experimental test groups in which one control and two conditioning systems based on moisture damage application were created. Indirect tension strength test for cracking resistance was conducted at 10 degrees C and 20 degrees C, while indirect tension strength test and indirect tension test were carried out at 20 degrees C in three loaded periods to investigate the load distribution capacity of mixtures and moisture damage problem. It was understood that both additives ameliorated the mechanical characteristics according to the traditional mixtures. SBS modified mixtures showed higher resilient modulus value than the amine modified ones and proved higher cracking resistance in general. Regarding moisture damage, SBS modified mixtures have higher performance for high loading periods and excessive conditioning systems.
Keywords: conditioning systems; water damage; SBS; fatty amine; MIXTURES; LIME; Engineering